2018
DOI: 10.1002/jcp.27637
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of sorafenib with mesenchymal stem cells as a novel cancer treatment regimen in xenograft models of hepatocellular carcinoma

Abstract: Aim Hepatocellular carcinoma (HCC) is the most common liver malignancy and the second leading cause of cancer‐related deaths in the world. Sorafenib is the first‐line treatment of HCC. Although sorafenib has positive effects on the survival of patients, novel therapeutic strategies are needed to extend survival and improve the efficacy of sorafenib. This study combines sorafenib with mesenchymal stem cells (MSCs) as a new approach to enhance the efficacy of sorafenib. Material and methods A subcutaneous xenogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…As illustrated in Fig. 7, Sorafenib induced no signi cant effect on the expression levels of perforin, granzyme, IFN-γ and IL-6 (p value > 0.05), however, it signi cantly down regulated both IL-1 and TNF-α and induced the expression of IL-10 (p value < 0.05), as have been reported in our previous study (31). Most importantly, the gene expression levels of all the intended gene were the lowest in the mice treated with the combination of NKC & Sor, indicating no synergic effect of NK cells and Sorafenib (at speci c dose and time) against HCC tumors.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…As illustrated in Fig. 7, Sorafenib induced no signi cant effect on the expression levels of perforin, granzyme, IFN-γ and IL-6 (p value > 0.05), however, it signi cantly down regulated both IL-1 and TNF-α and induced the expression of IL-10 (p value < 0.05), as have been reported in our previous study (31). Most importantly, the gene expression levels of all the intended gene were the lowest in the mice treated with the combination of NKC & Sor, indicating no synergic effect of NK cells and Sorafenib (at speci c dose and time) against HCC tumors.…”
Section: Discussionsupporting
confidence: 81%
“…(27). All experimental procedures were performed according to the National Institutes of Health (NIH) guide for the care and use of Laboratory animals and were approved by the Institutional Ethical Committee of Tehran University (IECTU) of Medical Sciences (IR.TUMS.VCR.REC.1397.181) (28).…”
Section: Cell Lines and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusionally, the anti-tumor and anti-metastatic features of MSCs are retained by combined with sorafenib. 29,30 The inhibitory effect of MSCs-CM on the growth of liver cancer cells has been reported in several pieces of literature. Seyhoun et al further found that sorafenib combined with MSCs-CM also has a negative result on the growth of liver cancer cells.…”
Section: Mscs and Sorafenibmentioning
confidence: 99%
“…The collected tumor tissues were used for further molecular studies. Cell apoptosis and proliferation in tumor tissues were measured by terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) staining with in situ cell death detection kit (Roche, Mannheim, Germany) or Ki67 immunohistochemistry with anti-Ki67 antibody (ab16667, 1:1000 dilution, Abcam) following the manufacturer's instructions as previous study 20 .…”
Section: Murine Xenograft Modelmentioning
confidence: 99%